2020
DOI: 10.1590/s1980-220x2018040103546
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, anxiety and depression in head and neck cancer patients: a randomized clinical trial

Abstract: OBJECTIVE To evaluate an educational program based on the principles of self-management with a conventional educational program through quality of life, anxiety and depression instruments within 12 months of starting cancer treatment. METHOD An experimental, randomized, controlled study conducted with head and neck cancer patients treated at a university hospital in the city of São Paulo, Brazil. Patients were randomly divided into two groups: the control group submitted to the conventional educational plan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
6
1
1
Order By: Relevance
“…Previous studies have noted that emotional distress (anxiety and depression) tends to lessen over time for many patients in United States, Europe (e.g., London, Sweden and Netherland) and also in Brazil 6,7,14–16,21–24 . However, despite the fact that the current study noted a similar trend in Brazil, by the end of the chemotherapy treatment, there were still a great number of patients experiencing moderate to severe distress.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Previous studies have noted that emotional distress (anxiety and depression) tends to lessen over time for many patients in United States, Europe (e.g., London, Sweden and Netherland) and also in Brazil 6,7,14–16,21–24 . However, despite the fact that the current study noted a similar trend in Brazil, by the end of the chemotherapy treatment, there were still a great number of patients experiencing moderate to severe distress.…”
Section: Discussioncontrasting
confidence: 71%
“…This evidence has led to the development of standards of care advocated by national organizations, such as the American College of Surgeons' Commission on Cancer and the National Comprehensive Cancer Network 13 . However, this evidence base has primarily emerged from distress at the time of diagnosis based on patients from high‐income countries (e.g., United States and Canada), with some studies documenting distress throughout the course of treatment in other countries 14–17 . It is important to highlight the challenges faced in low‐ and middle‐income countries (LMICs); for years there has been an increase in the number of patients diagnosed with cancer, along with mortality rates of certain cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Issues with employment are significantly associated with poor quality of life among patients as reflected by high levels of anxiety and social avoidance 95 . Clearly, there is a need for health care providers to comprehend and explore the expressions of depression, anxiety and building self-management skills in oral cancer patients in order to provide better quality of life 96,97 .…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression are also prevalent problems in cancer patients. The study conducted by Hortense et al indicated that anxiety and depression also had correlations with participants' QoL [37]. The RTspeci c symptom cluster and gastrointestinal symptom cluster were crucial clusters for managing HNC patients with RT, so healthcare professionals should focus limited medical resources on these NISs to improve patients' nutritional status and QoL.…”
Section: Discussionmentioning
confidence: 99%